Advanced FDTD methods : parallelization, acceleration, and engineering applications - Yu, Wenhua (Artech House electromagnetic analysis series., 2011)
The finite-difference time-domain (FDTD) method has revolutionized antenna design and electromagnetics engineering. Here's a cutting-edge book that focuses on the performance optimization and engineering applications of FDTD simulation systems. Covering the latest developments in this area, this unique resource offer you expert advice on the FDTD method, hardware platforms, and network systems. Moreover the book offers guidance in distinguishing between the many different electromagnetics software packages on the market today. You also find a complete chapter dedicated to large multi-scale problem solving. This practical reference is supported with 250 illustrations, 128 equations, and 11 appendixes filled with helpful data processing techniques related to the FDTD method.